BRCA1‐2 diagnostic workflow from next‐generation sequencing technologies to variant identification and final report. Issue 10 (4th July 2016) - Pilato, Brunella; Pinto, Rosamaria; De Summa, Simona; Petriella, Daniela; Lacalamita, Rosanna; Danza, Katia; Paradiso, Angelo; Tommasi, Stefania
Abstract : The BRCA1‐BRCA2 genes predispose to hereditary breast and ovarian cancer, and the germline and mutational status of these genes defines a target population that can benefit from PARP inhibitor treatments. To respond to the increasing number of BRCA1‐BRCA2 tests, it is necessary to shift to high‐throughput technologies that are reliable and less time consuming. Different methodological platforms are dedicated to this purpose with different approaches and algorithms for analysis. Our aim was to set up a cost‐effective and low time‐consuming BRCA1‐BRCA2 mutation detection workflow using the Ion Torrent PGM technology. A retrospective cohort of 40 patients with familial breast/ovarian cancer previously tested by Sanger sequencing and a prospective cohort of 72 patients (validation set) were analyzed. The validation set included 64 patients affected by familial breast/ovarian cancer and eight sporadic ovarian cancer cases, who are potential candidates for PARPi treatments. A complete and standardized workflow easily usable and suitable in a certified laboratory has been proved and validated. This includes all steps from library preparation to the final report. The use of next‐generation sequencing will be of benefit for patients enrolled in the genetic counseling process and, moreover, will enhance the process of selecting patients eligible for personalized treatments. © 2016 Wiley Periodicals, Inc.